2013
DOI: 10.3168/jds.2012-6305
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of day-to-day variation in behavior for the automated detection of lameness in dairy cows

Abstract: Lameness is a major problem in modern dairy husbandry and has welfare implications and other negative consequences. The behavior of dairy cows is influenced by lameness. Automated lameness detection can, among other methods, be based on day-to-day variation in animal behavior. Activity sensors that measure lying time, number of lying bouts, and other parameters were used to record behavior per cow per day. The objective of this research was to develop and validate a lameness detection model based on daily acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 19 publications
0
42
0
1
Order By: Relevance
“…Previous studies have reported, that lameness affects cow behaviour: lame cows may lie down longer around feeding (Yunta et al, 2012), have longer daily lying-time (Blackie et al, 2011), longer lying bouts (Thomsen et al, 2012) and take fewer steps/day (de Mol et al, 2013). In addition, using data from automated feed stations, lameness has been found to decrease feeding time (Gonzàlez et al, 2008).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have reported, that lameness affects cow behaviour: lame cows may lie down longer around feeding (Yunta et al, 2012), have longer daily lying-time (Blackie et al, 2011), longer lying bouts (Thomsen et al, 2012) and take fewer steps/day (de Mol et al, 2013). In addition, using data from automated feed stations, lameness has been found to decrease feeding time (Gonzàlez et al, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…Thus, some studies have used pedometers or the more advanced accelerometers as stand-alone technology to detect lameness (Mazrier et al, 2006;Alsaaod et al, 2012). Others have combined activity data with additional types of sensor data such as milk yield, concentrate left-overs or milking order to detect lameness (de Mol et al, 2013;Kamphuis et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In the threshold setting of Pastell and Kujala (2007), Ito et al (2010) and Viazzi et al (2013Viazzi et al ( , 2014, the group of non-lame cows included the mildly lame cows (locomotion score 2) which were considered in a separate group in our study. de Mol et al (2013) disregarded the mildly lame cows (locomotion score 2) and tested his detection model for non-lame and severely lame cows (locomotion 3 or more). Poursaberi et al (2010) developed an algorithm based on the arched back posture of cows using computer vision techniques with a 2D-camera (side view).…”
Section: Group Based In the Locomotion Scores Of Trained Expertmentioning
confidence: 99%
“…The specific analysis reported has varied in the literature. The most common measures reported are receiver operator characteristic curve, area under the curve (Kamphuis et al, 2013;Alsaaod et al, 2017), confusion matrices (Martiskainen et al, 2009;Van Hertem et al, 2013), and specificity, sensitivity, positive predictive value, and accuracy (de Mol et al, 2013;Van Hertem et al, 2013).…”
Section: Assessing Lameness Detection Performancementioning
confidence: 99%